TEI-encoding of text reuses in the BIBLINDEX Project - Hue-Gay, Elysabeth; Mellerin, Laurence; Morlock, Emmanuelle (Journal of data mining and digital humanities, 2017)
This paper discusses markup strategies for the identification and description of text reuses in a corpus of patristic texts related to the BIBLINDEX Project, an online index of biblical references in Early Christian Literature. In addition to the development of a database that can be queried by canonical biblical or patristic references, a sample corpus of patristic texts has been encoded following the guidelines of the TEI (Text Encoding Initiative), in order to provide direct access to quoted and quoting text passages to the users of the https://www.biblindex.info platform.